PARTISIPASI POLITIK MASYARAKAT DALAM PEMILIHAN KEPALA DAERAH ( PILKADA ) KONAWE UTARA - Muh. Asdar Maknung; Andi Awaluddin Ma'ruf (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Kendari, 2022)
The purpose of this study is to see how the community's political participation in the regent election in Basule Village, sub-district. Lasolo kab. Konawe Utara and to look at the factors that influence the political participation of the community in the regent election in Basule Village, sub-district. Lasolo kab. Konawe Utara. The method used in this study is qualitative with a descriptive form, the subjects in this study are the Village Head, Community Leader, and Youth Leader. Techniques in collecting this data are observation, interviews, documentation. The results of this study can be concluded that the form of community political participation can be used as a measure to assess the stability of the political system of citizen satisfaction and dissatisfaction which refers to the high and low level of community political participation in the general election for regional heads, the community actively uses their voting rights in carrying out the general election. regions and participate in political activities. Factors that influence public political participation in regional head elections are the factors of public awareness and trust in the government regarding public knowledge about politics. Efforts to participate in community politics in the general election of regional heads in carrying out socialization activities, the village government has been very maximal in disseminating the implementation of election activities to the community.